EKSTRAK GLUKOMANAN UMBI SUWEG (Amorphophallus campanulatus) ASAL PIDIE JAYA SEBAGAI BAHAN SEDIAAN MASKER ORGANIK YANG DIPERKAYA SERBUK DAUN KELOR - Fazli, Rahmad Rizki; Hendriani, Rosa; Erlidawati, Erlidawati; Alvionita, Mieke (Lantanida Journal, 2025)
The combination of D-mannose and D-glucose with β-1,4-glycosidic bonds with a ratio of 1.6:1 forms a straight chain polymer of glucomannan. Glucomannan flour is widely used in industry to make paper, adhesives, food ingredients, cosmetics, and cleaners. An organic mask preparation from glucomannan flour enriched with moringa leaf powder has been made from suweg tubers from Pidie Jaya, which is expected to be widely used, one of which is as a cosmetic ingredient. The purpose of this study was to determine the glucomannan content in suweg tubers from Pidie Jaya and to obtain the best formula of an organic mask based on panelist preferences. Glucomannan flour was extracted with 60% ethanol solvent and the glucomannan content test was carried out using the DNS method. The formulation of organic mask preparations includes glucomannan flour, moringa leaf powder, and H2O with different concentration ratios, namely F1 (50% glucomannan flour: 50% moringa leaf powder), F2 (75% glucomannan flour: 25% moringa leaf powder) and F3 (25% glucomannan flour: 75% moringa leaf powder). Then the physical properties were tested including pH test, homogeneity test, spreadability test, drying time test, and organoleptic test. The results of the study obtained a glucomannan content of 26.39%. The results of organoleptic testing showed that users preferred organic mask preparations from glucomannan flour enriched with moringa leaf powder formula F1 (50% glucomannan flour and 50% moringa leaf powder) both in terms of color, texture, odor/aroma, and general preference.